Reimagining Gender Equity through Legislation: A Discourse Analysis on Post-Colonial Feminist Critique of the 2024 Affirmative Action Bill - Akla, Ali Dan (Journal of Language and Literature Studies, 2025)
This study examines the 2024 Affirmative Action Bill through a post-colonial feminist lens, critically evaluating its potential to confront and address systemic gender inequities embedded within Ghana’s Fourth Republic’s political and socio-cultural structures. Drawing on post-colonial feminist theory, the research situates the bill within broader historical and ideological continuities of gendered marginalization, contending that meaningful equity demands the dismantling of both colonial legacies and entrenched patriarchal norms. Employing qualitative methods comprising textual analysis and content analysis, the study interrogates policy texts, historical documents, and feminist scholarship to uncover the bill’s transformative possibilities and limitations. The analysis is grounded in a qualitative study, employing textual analyses. Postcolonial feminist theory, Critical Discourse Analysis, and Indexicality, are employed as blueprints in navigating the textual analyses, focusing on how the bill’s legal language, cultural references, and policy metaphors encode ideological assumptions about gender, power, and identity. The primary data corpus is the 2024 Affirmative Action Bill itself, while the feminine class in Ghana serves as the implied population whose experiences, representation, and structural positioning the study seeks to evaluate. The findings reveal that while the 2024 bill marks a progressive legislative milestone, its long-term success depends on sustained investment in female education, civic engagement, and the reshaping of national gender narratives. The study recommends a multi-pronged approach to gender equity—one that integrates inclusive policy implementation, public education, and institutional reform as core strategies for embedding lasting transformation within Ghana’s democratic development. The study’s findings urge policymakers to adopt targeted gender-responsive frameworks that not only legislate equity but actively transform entrenched socio-cultural biases through sustained educational and legal reforms.